2011
DOI: 10.1145/1952982.1952994
|View full text |Cite
|
Sign up to set email alerts
|

Remote data checking using provable data possession

Abstract: We introduce a model for provable data possession (PDP) that can be used for remote data checking: A client that has stored data at an untrusted server can verify that the server possesses the original data without retrieving it. The model generates probabilistic proofs of possession by sampling random sets of blocks from the server, which drastically reduces I/O costs. The client maintains a constant amount of metadata to verify the proof. The challenge/response protocol transmits a small, constant amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
249
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(249 citation statements)
references
References 40 publications
0
249
0
Order By: Relevance
“…A publicly verifiable remote data integrity checking architecture [7,11,14] for security cloud storage is illustrated in Fig 1. Three different entities, namely, the cloud user, the cloud server and the third party auditor (TPA) are involved in the system. The cloud user has large amount of data to be stored on the cloud server without keeping a local copy, and the cloud server has significant storage space and computation resources and provides data storage services for cloud users.…”
Section: Remote Data Integrity Checking For Secure Cloud Storagementioning
confidence: 99%
See 1 more Smart Citation
“…A publicly verifiable remote data integrity checking architecture [7,11,14] for security cloud storage is illustrated in Fig 1. Three different entities, namely, the cloud user, the cloud server and the third party auditor (TPA) are involved in the system. The cloud user has large amount of data to be stored on the cloud server without keeping a local copy, and the cloud server has significant storage space and computation resources and provides data storage services for cloud users.…”
Section: Remote Data Integrity Checking For Secure Cloud Storagementioning
confidence: 99%
“…Blum presented a scheme enabling data owners to verify the integrity of remote data without explicit knowledge of the entire data [5]. Provable data possession (PDP) [6,7], introduced by Ateniese et al, is a technique for validating data integrity over remote servers. In a typical PDP system, the data owner generates some metadata for a file, which will be used later for integrity checking via a challenge-response protocol with the remote server.…”
Section: Introductionmentioning
confidence: 99%
“…Although spot-checking is suitable for detecting large corruptions, it is vulnerable to small corruptions against the entire data size. This problem has been resolved by introducing the notion of δ-robustness, which adopts forward error correction (FEC) codes such as the Reed-Solomon (RS) code [4]- [6] (δ-robustness will be defined in Sect. 2.1.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with traditional cryptographic techniques for data integrity, secure auditing is much more practical for verifying data storage correctness. In 2007, Ateniese et al proposed the notion of provable data possession (PDP) [7,8] to check the integrity of remote data. Ateniese et al [9] also demonstrated how to construct data auditing schemes from homomorphic identification protocols.…”
Section: Introductionmentioning
confidence: 99%